2014
DOI: 10.1542/peds.2013-4285
|View full text |Cite
|
Sign up to set email alerts
|

Weighted Blankets and Sleep in Autistic Children—A Randomized Controlled Trial

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Children with autism sleep poorly compared with their peers. Sensory integration, including use of weighted blankets, is proposed as a means to reduce arousal and stress. There is, however, no evidence that weighted blankets can improve sleep for these children. WHAT THIS STUDY ADDS:This is the first robust study to evaluate the impact of weighted blankets and show that they do not improve sleep parameters in children with autism spectrum disorder. abstract OBJECTIVE: To assess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
84
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(91 citation statements)
references
References 22 publications
6
84
1
Order By: Relevance
“…All RCTs were assessed as having high risk of bias for most items on the Cochrane Risk of Bias tool because of issues with randomization and incomplete outcome data. We were unable to find a registered protocol for 10 RCTs, and in all RCTs blinded outcome assessment was either not undertaken or it was unclear whether blinding had occurred . However, we do note that the type of interventions and outcomes under investigation make robust, blinded outcome assessment challenging.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All RCTs were assessed as having high risk of bias for most items on the Cochrane Risk of Bias tool because of issues with randomization and incomplete outcome data. We were unable to find a registered protocol for 10 RCTs, and in all RCTs blinded outcome assessment was either not undertaken or it was unclear whether blinding had occurred . However, we do note that the type of interventions and outcomes under investigation make robust, blinded outcome assessment challenging.…”
Section: Resultsmentioning
confidence: 99%
“…Two RCTs and four before‐and‐after studies evaluated other types of non‐pharmacological intervention (Tables and ) …”
Section: Resultsmentioning
confidence: 99%
“…We know there is a high heritability for polymorphisms in the melatonin synthesis pathway (N‐acetyl serotonin and acetylserotonin O‐methyltransferase), which may influence the sleep cycles in these children . There is good evidence that weighted blankets do not improve sleep onset or total sleep time in children with ASD …”
Section: Sleep Problems and Their Treatment In Specific Disordersmentioning
confidence: 99%
“…Several studies have substantiated parent-reported sleep problem reports using more objective measures of actigraphy and PSG (Goldman, Richdale, et al, 2012; Malow et al, 2006; Wiggs & Stores, 2004). However, several studies also note parent reports of sleep problems are higher than those specified using behavioral criteria (Goodlin-Jones et al, 2009; Gringras et al, 2014; Schreck & Mulick, 2000). For example, in a study of young children with ASD, other (non-ASD) developmental disabilities (DD), and no known diagnosis, Goodlin-Jones and colleagues reported elevated sleep problems via parent report in both the DD and ASD groups but only found elevated behaviorally defined sleep problems (e.g., frequent night awakenings) in the DD group (Goodlin-Jones, Tang, Liu, & Anders, 2009).…”
Section: Syndrome/condition Specific Sleep Problemsmentioning
confidence: 99%